2017
DOI: 10.3233/bmr-150501
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of foot morphology and their relationship to gender, age, body mass index and bilateral asymmetry in Japanese adults

Abstract: This study showed that gender has a bigger impact on length, width, height and girth parameters of foot than BMI or age. BMI has an impact on both arch height and stiffness. Besides, bilateral asymmetry affects values of height parameters of foot and arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
2
31
0
1
Order By: Relevance
“…Mahshid et al reported that Japanese women had narrower feet in the heel and forefoot, and their instep, rst and fth toes and navicular height were also lower than men's [27]. Zhao et al demonstrated that Japanese men generally had longer, larger and higher arched feet than women [28]. Since we adjusted the shoe size to 25.5 cm and compared, it was considered that foot morphology had little effect on peak pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Mahshid et al reported that Japanese women had narrower feet in the heel and forefoot, and their instep, rst and fth toes and navicular height were also lower than men's [27]. Zhao et al demonstrated that Japanese men generally had longer, larger and higher arched feet than women [28]. Since we adjusted the shoe size to 25.5 cm and compared, it was considered that foot morphology had little effect on peak pressure.…”
Section: Discussionmentioning
confidence: 98%
“…Mahshid et al reported that Japanese women had narrower feet in the heel and forefoot, and their instep, rst and fth toes and navicular height were also lower than men's [27]. Zhao et al demonstrated that Japanese men generally had longer, larger and higher feet than women [28]. Since we adjusted the shoe size to 25.5 cm and compared, it was considered that foot morphology had little effect on peak pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Given the high reliability and low SEM for most of the parameters, a direct validation of the measurements against measurements made by using medical images will be needed for future applications that required accurate data for decision-making, such as in a clinical setting. Further studies may also include more parameters based on the reconstructed weight-bearing 3D sole surface measured by the current approach, such as the distances of the first and fifth metatarsophalangeal joints to the sustentaculum tali, great toe height, distal end of the first toe and instep height [15,16,53,54], and may determine their test-retest reliabilities. One senior and one junior rater were used in the current study following previous protocols [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Several parameters quantifying the sole morphology have been proposed and used in the literature and clinical practice, such as foot length (FL) [9], foot width (FW) [10], arch height (AH), normalized arch height (NAH), arch index (AI) [11], Staheli's arch index (SAI) [12], Chippaux-Smirak index (CSI) [13], hallux valgus angle (HVA) [14], minimal distance between hallux and other toes, great toe height, and instep height, etc. [15,16]. Among these parameters, those related to the medial longitudinal arch have received much research attention because the medial longitudinal arch is one of the most important features of the foot structure, relating to the absorption of ground forces and propulsion.…”
Section: Introductionmentioning
confidence: 99%